Analysis of the Effectiveness of Dispute Resolution Mechanisms: A Case Study of PT. Bank Muamalat Indoneisa and PT. General Takaful Economy - Oktaviany, Mega; Ashary, Ade Rangga Putra; Nordin, Nadhirah (Tasharruf: Journal Economics and Business of Islam, 2024)
This paper explains how arbitration functions in the Indonesian legal system. The purpose of this study is to determine whether there is a legal remedy that can be made by law to reach a final decision based on the principle of final and binding. This study aims to study the way sharia arbitration bodies handle economic disputes. The research method used is juridical-normative, using descriptive qualitative analysis. The results showed that, as an extra-judicial institution governed by international law that has been ratified by the Indonesian government, arbitration helps complement the Indonesian judicial system. And the absence of a legal remedy for a final award in accordance with the principles of final and binding And the absence of legal remedies for a final decision in accordance with the principle of finality and binding is one of the advantages of settlement through arbitration compared to the court, In conclusion arbitration is more effective in resolving sharia insurance disputes based on the principle of simple, fast, and cheap justice according to the mandate of the Law.